Kasus Kerusuhan Tanjung Priok Tahun 1984 Sebagai Pelanggaran HAM di Indonesia. - Jonathan, Kevin; Taslim, Naomi Yoanna; Dinata, Chindy Melvin; Matthew (Nusantara: Jurnal Pendidikan, Seni, Sains dan Sosial Humaniora, 2023)
Human rights are basic rights that are inherently inherent in human beings, universal and lasting, therefore they must be protected, respected, defended, and must not be ignored, reduced, or deprived by anyone. Human rights violations are still a sensitive and major issue in Indonesian society. Until then until now human rights violations are still a frequent problem. One of the largest cases of human rights violations that occurred during the New Order period was the Tanjung Priok Case that occurred on September 12, 1984 in Tanjung Priok, North Jakarta, committed by the military government against Tanjung Priok residents. The Tanjung Priok tragedy was filled with gunfights that left 24 people dead and 55 injured. Meanwhile, the National Solidarity investigation into the Tanjung Priok (Sontak) incident concluded that the death toll reached 400 people, not including the disabled and injured. This research was conducted using qualitative methods in a descriptive analytical manner through historical, sociological, and juridical approaches. Qualitative research method is a method used to examine the natural condition of objects. Descriptive research is conducted to determine the value of independent variables without making comparisons with other variables (Sugiyono, 2018). The data obtained is presented in a descriptive analytical manner, which is an analytical technique that explains the characteristics of the variables that are the focus of the researcher. This type of research is literature research, which is research that uses literature such as books, notes, and reports on existing research results. The Human Rights Court in the Tanjung Priok case has tried 14 defendants who are suspected of being responsible in this case. A total of 12 people were found guilty of gross human rights violations and sentenced. While 2 other people were found not guilty in this incident.